2021
DOI: 10.15252/msb.202110280
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fluxes for nutritional flexibility of Mycobacterium tuberculosis

Abstract: The co-catabolism of multiple host-derived carbon substrates is required by Mycobacterium tuberculosis (Mtb) to successfully sustain a tuberculosis infection. However, the metabolic plasticity of this pathogen and the complexity of the metabolic networks present a major obstacle in identifying those nodes most amenable to therapeutic interventions. It is therefore critical that we define the metabolic phenotypes of Mtb in different conditions. We applied metabolic flux analysis using stable isotopes and lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…Similar isotopologue analyses have been successfully applied across various host-pathogen models to measure intracellular metabolism of these pathogens, such as 13 C glucose profiles of M. leprae growing in Schwann cells (70) and Trypanosoma brucei in bloodstream form (71) and 13 C glycerol profiles in legionella pneumophila replicating in macrophages (72). 13 C-isotopic analysis of Mtb in vitro cultures in a chemostat setup at controlled growth rate demonstrated efficient isotope incorporation and co-catabolism of 13 C-labelled acetate and cholesterol, which are intracellular nutrient sources for Mtb (73). Recent advances in MS technologies have enabled the use of several stable isotopes including both single and mixed labelled species such as 15 N and 2 H. 2 H cholesterol labelling of Mtb in vitro cultures confirmed that Mtb utilized cholesterol to synthesize amino acids (73).…”
Section: Metabolomics and Isotopic Tracing Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar isotopologue analyses have been successfully applied across various host-pathogen models to measure intracellular metabolism of these pathogens, such as 13 C glucose profiles of M. leprae growing in Schwann cells (70) and Trypanosoma brucei in bloodstream form (71) and 13 C glycerol profiles in legionella pneumophila replicating in macrophages (72). 13 C-isotopic analysis of Mtb in vitro cultures in a chemostat setup at controlled growth rate demonstrated efficient isotope incorporation and co-catabolism of 13 C-labelled acetate and cholesterol, which are intracellular nutrient sources for Mtb (73). Recent advances in MS technologies have enabled the use of several stable isotopes including both single and mixed labelled species such as 15 N and 2 H. 2 H cholesterol labelling of Mtb in vitro cultures confirmed that Mtb utilized cholesterol to synthesize amino acids (73).…”
Section: Metabolomics and Isotopic Tracing Studiesmentioning
confidence: 99%
“…13 C-isotopic analysis of Mtb in vitro cultures in a chemostat setup at controlled growth rate demonstrated efficient isotope incorporation and co-catabolism of 13 C-labelled acetate and cholesterol, which are intracellular nutrient sources for Mtb (73). Recent advances in MS technologies have enabled the use of several stable isotopes including both single and mixed labelled species such as 15 N and 2 H. 2 H cholesterol labelling of Mtb in vitro cultures confirmed that Mtb utilized cholesterol to synthesize amino acids (73). 15 N-asparagine was used to measure the uptake and assimilation of nitrogen in murine macrophages using NANO-Secondary ion mass spectrometry (SIMS) (74).…”
Section: Metabolomics and Isotopic Tracing Studiesmentioning
confidence: 99%
See 3 more Smart Citations